A. S. Puškin im Uebersetzungswerk Henry von Heiselers (1875-1928) Ein europaeischer Wirkungsraum der Petersburger Kultur - Poljakov, Fedor B. (Slavistische Beitraege, 1999)
Two contributions here are seeking access to the continuation of a temporarily buried Petersburg tradition in a European space on the example of the German-speaking poet Henry von Heiseler. That "his" Puškin is to be understood in this frame of interpretation as a cultural symbol with identity-forming and dialogical potential and not just as a "translat" reflects the positions of the said translator.